2016
DOI: 10.1002/cam4.646
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer after false‐positive results in mammographic screening

Abstract: Women with false‐positive results are commonly referred back to routine screening. Questions remain regarding their long‐term outcome of breast cancer. We assessed the risk of screen‐detected breast cancer in women with false‐positive results. We conducted a joint analysis using individual level data from the population‐based screening programs in Copenhagen and Funen in Denmark, Norway, and Spain. Overall, 150,383 screened women from Denmark (1991–2008), 612,138 from Norway (1996–2010), and 1,172,572 from Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…This latter result highlights one aspect of the potential clinical relevance of the gist signal since it is well known that women who have cancer in one breast are more likely to have future cancer in the other breast 20 . It has also been shown that women recalled at screening by radiologists who felt there was something wrong but could not localise any cancer assessment, have a 1.4–6.6 fold increased risk of developing aggressive and larger cancers (≥20 mm) within 3–10 years compared to those who were not recalled 21 , 22 . This evidence suggests that a gist signal could be predictive of future cancer if it was visible in a mammogram with no visible overt signs of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This latter result highlights one aspect of the potential clinical relevance of the gist signal since it is well known that women who have cancer in one breast are more likely to have future cancer in the other breast 20 . It has also been shown that women recalled at screening by radiologists who felt there was something wrong but could not localise any cancer assessment, have a 1.4–6.6 fold increased risk of developing aggressive and larger cancers (≥20 mm) within 3–10 years compared to those who were not recalled 21 , 22 . This evidence suggests that a gist signal could be predictive of future cancer if it was visible in a mammogram with no visible overt signs of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We ask the reader to note that resources saved by cutting suboptimal testing in low‐risk groups may justify spending more resources on high‐risk groups. Intensified screening has been proposed for women with high mammographic density and for women with false‐positive screening results …”
Section: Introductionmentioning
confidence: 99%
“…BREAST IMAGING: Breast Cancer after False-Positive Findings at Mammography Hofvind et al analyses (7)(8)(9). Recent studies (19)(20)(21)(22)(23) showed an increased risk of subsequent screening-detected breast cancer after a previous false-positive screening. An increased risk of IBC might also be expected after a false-positive screening versus a negative screening.…”
mentioning
confidence: 99%